A case series and review of canine idiopathic osteonecrosis of the jaw - Rossi, Amy; Anderson, Jamie G. (Frontiers in Veterinary Science, 2025)
Idiopathic osteonecrosis of the jaw in dogs is a rare disease. Research into human osteonecrosis of the jaw has increased considerably in recent years revealing numerous underlying risk factors and comorbidities. The goal of this case series was to evaluate similar risk factors and comorbidities in dogs. The medical records from 10 cases were retrospectively reviewed for patient signalment, diagnostic results and treatment. Most cases had either cone beam or conventional computed tomography performed which allowed a detailed evaluation of maxillofacial structures. In this cohort, lesions had a predilection for the caudal maxilla and ipsilateral zygomatic arch and dental surgery did not always precede development of lesions. More cases and additional diagnostics will be needed to uncover the etiology of this disease.